The impact of participation in sports on educational attainment: new evidence from Germany - Thomas Cornelißen; Christian Pfeifer (Institute for the Study of Labor (IZA), 2007)
We analyze the impact of exercising sports during childhood and adolescence on educational attainment. The theoretical framework is based on models of allocation of time and educational productivity. Using the rich information from the German Socio-Economic Panel (GSOEP), we apply generalized ordered probit models to estimate the effect of participation in sport activities on secondary school degrees and professional degrees. Even after controlling for important variables and selection into sport, we find strong evidence that the effect of sport on educational attainment is statistically significant and positive.
Keywords: I21; 330; Allocation of time; education; human capital; sport; Sport; Bildungsverhalten; Bildungsniveau; Bildungsabschluss; Deutschland